Peran Perkumpulan Pengajian sebagai Potensi Pembangunan Masyarakat Islam dalam Mencegah Tindakan Kriminalitas di Desa Bandar Masilam II Kecamatan Bandar Masilam Kabupaten Simalungun - Kurnia Hanum (Al-Balagh : Jurnal Komunikasi Islam, 2024)
This study discusses the role of religious study groups as a potential for Islamic community development in preventing criminal activities in Bandar Masilam II Village, Bandar Masilam District, Simalungun Regency. In this context, religious study groups function as platforms to deepen religious understanding, build moral values, and promote social awareness. The study utilizes a qualitative research method with a sociological approach. The informants for this study are the female participants of the study groups. Data collection techniques include interviews, field observations, and documentation. Religious study groups have great potential in assisting the Islamic community in preventing criminal activities. The study groups in Bandar Masilam II Village are one form of religious activities conducted every Friday that facilitate learning and understanding of Islamic teachings. The main roles of these study groups in preventing criminal activities in Bandar Masilam II Village include conveying moral and ethical values, fostering spiritual development, promoting social empowerment, conflict resolution, channeling positive energy, empowering women and youth, as well as social supervision and reintegration. During the implementation of the study groups as a potential for Islamic community development in preventing criminal activities in Bandar Masilam II Village, there are supporting factors and hindering factors. The supporting factors include strong religious education, positive social environment, Islamic legal education, social awareness, and concern. The hindering factors include lack of awareness and religious education, limited involvement of the youth, internal conflicts, and lack of resources